Development of breed preference index for pure-bred dogs - V. Rajaganapathy, Raghy Radhakrishnan, D. Sreekumar S. Ramkumar, Ninan Jacob (Indian Journal of Animal Production and Management, 2020)
A study was carried out to assess the preference of the dog owners for different breeds of dogs, the factorsinfluencing breed preference by the dog owners and to develop a Breed Preference Index (BPI). It was foundthat the most preferred breed of dog in Puducherry was Labrador retriever, followed by Doberman pinscher,German Shepherd Dog, Beagle, Boxer, Dachshund, Mastiff, English Cocker Spaniel, Pug, Great Dane,Golden retriever and Pomeranian. The major factors that influenced breed preference were activeness,general appearance, size and utility. Activeness was the first factor for preference in breeds like GermanShepherd Dog, Pug and Spitz, whereas general appearance was the main factor for preference in Labradorand Great Dane. Utility as a guard dog formed the main factor for preferring Doberman. Size matteredin Dachshund; which was the main reason for preferring the breed. The other factors that influenced thepreference of dogs were coat, good with children, easy to handle, cost, ears and eyes; though at a low level.